Pengaruh Struktur Modal, Profitabilitas, dan Struktur Aktiva terhadap Harga Saham - Sellytyanengsih E. Churcill; Kenny Ardillah (STATERA: Jurnal Akuntansi dan Keuangan, 2019)
The purpose of this research is to examine the influence of profitability, capital structure, and asset structure positively to the stock price on manufacture companies which are listed in Indonesia Stock Exchange (IDX). The research samples have been selected by using purposive sampling technique to the 62 manufacture companies have been published the financial statement and active stocks which have been traded at Indonesia Stock Exchange (IDX) in 2014 – 2016 periods with the amount of 186 data which have yet to be the research sample criteria.The data analysis has been carried out by using multiple linier regressions analysis. The results of the study found out that capital structure has a positive influence on stock price means that the high capital structure influences shareholder decisions in increasing stock price. Profitability has a significant positive influence on stock price means that every increase in the profitability of a food and beverages company, it causes the stock price will increase. And asset structure have a positive influence on stock price means to indicate that every increase in asset structure of manufacture company, it causes that stock price will increase.